Migrasi Desa-Kota di Indonesia: “Risk Coping Strategy VS Investment” - Marta, Joan; Fauzi, Akhmad; Juanda, Bambang; Rustiadi, Ernan (UI Scholars Hub, 2020)
The study aims to analyses the reasons behind migrations motives among rural household based on household and area origin characteristic. The study used IFLS data of 2007 and 2014 consisting 2,581 household samples spreading in 13 provinces. Binomial and multinomial logit model was used to estimate probability to migrate based on migration motive. We found the contradictory effect of household income on decision to migrate between motives. Income has negative effect in risk coping as migration motives, otherwise have positive effect in investment motive.